Ileo-ileal Intussusception and Bowel Obstruction Caused by Plasmablastic Lymphoma of Small Bowel- A Rare Entity in Rare Location - Kulkarni, Aditya Atul (J Clin Diagn Res, 2016)
Intussusception of small bowel is considered a rare cause of bowel obstruction in adults accounting for only about 1% of bowel obstruction in adults. Intussusception in adults is uncommon with 95% cases of intussusceptions occurring in children. Adult intussusception from small intestinal lymphoma is also rare with only 36 cases reported in the literature between 2000 and 2011. Plasmablastic lymphoma (PBL) is an aggressive lymphoid neoplasm usually seen in the oral cavity in the clinical setting of human immunodeficiency virus (HIV) infection. Plasmablastic lymphoma of the small intestine is extremely rare. Here, we report a case of plasmablastic lymphoma of small bowel with ileoileal intussusception in an HIV-negative immunocompetent male patient.